Explorative Study of M-Commerce As a Small Business Innovation Strategy - Idris Idris; Khofifatu Rohmah Adi; Agung Wiradimadja (Indonesian Journal of Business and Entrepreneurship (IJBE), 2020)
MSMEs have proven to be part of the national economic backbone and have survived the economic crisis that has occurred in Indonesia. However, MSMEs are required to continue to innovate in their business strategies in the rapid disruption of business. The purpose of this study is to explore the role of m-commerce in MSMEs' business innovation strategies. By a qualitative descriptive approach, this study conducted at the Tempe Chips Center in Sanan in Malang as a case study. This study used primary (informants) and secondary (works of literature) data as sources of data and collected by using observation, interview, and documentation and used purposive sampling in determining the informants. Triangulation tests carried out in order to check data from various sources in various ways and times. This study found that the use of social media and the marketplace as one of MSMEs' business strategies in marketing products is still less than optimal. Although almost all MSMEs businesses use the Whatsapp application in their business transaction processes, only a few are expanding the market through other media. In general, MSMEs are familiar with social media and the marketplace, but few of them can optimize it in marketing their products. Keywords: m-commerce, business strategy, business innovation, MSMEs